Impact of Extension Services Introduced to Vegetable Producers who are using Protected Agriculture at Southern West Bank – Palestine - Tamimi, Talat Abu Rajab; Atawneh, Haroon Mohamad (Journal of agricultural, environmental and veterinary sciences, 2019)
This research tries to discover the level of agricultural extension services that presented to the vegetable farmers in protected houses; it also tests the level of the benefits from these services with the check of the relation between the level of extension services and all the independent variables. The data collected through a survey from personal interviews. The survey was two parts, the first includes questions to check personal variable while the second includes 10 questions to test the extension services presented to vegetable farmers and other 10 questions to test the level of benefits from these services.The sample was farmers in southern West Bank – Palestine (Hebron and Bethlehem). The main findings were that the farmers disappointed by the introduced services and related to the wall posters and the extension films.The research concludes that there is a weakness in the level of the presented extension services. In addition, the level of benefits for farmers from these services is limited. The researches have recommended the importance of review the tools that used for agricultural extension services. In addition, to use the agricultural consultancy as an important tool in vegetable extension service.
Keywords: Agricultural Extension Services; Vegetables; Protected Farming System; Southern West Bank; Palestine